Developing a workshop model for high school mathematics teachers in constructing HOTS questions through the Pendidikan Matematika Realistik Indonesia approach - Edwar; Putri, Ratu Ilma Indra; Zulkardi; Darmawijoyo (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
Indonesia's Program for International Student Assessment (PISA) results from 2000 to 2018 are worrisome because they are at the bottom of the international rankings. This result illustrates the low quality of education in Indonesia, which correlates with the qualifications of teachers. The quality of education will increase proportionally to the proportion of teachers who possess the necessary skills. Therefore, this study aims to train teachers to improve their professionalism in developing HOTs questions using the Pendidikan Matematika Realistik Indonesia (PMRI) approach. Design research-type development studies with two stages, preliminary and formative evaluation, are utilized. The results of the workshop revealed that the teacher's competency scores in developing HOTs questions increased by 45.70% (before the workshop), 77.14% (workshop 1), and 85.70% (workshop 2), respectively. It is evidenced by the teacher's ability to develop HOTs questions with the characteristics of questions investigating number content within the local context of selling duku fruits (langsat), which is a typical fruit of the East Ogan Komering Ulu (OKU) Regency and with a high degree of difficulty. This research also affects students in that it can stimulate their critical thinking abilities.